Imagining An Ideal Podcast Listener. (2nd October 2019) - Sharon, Tzlil; John, Nicholas A.
ABSTRACT: Based on a close reading of the adult coloring book and listening party kit published to accompany NPR's podcast Invisibilia, this article examines the ideal listener of, and the ideal mode of listening to, audio storytelling podcasts. We argue that these texts prompt the notion of childlike listening, a mode of listening that harnesses the innocence and curiosity of the child for the sake of deep discussion and interpersonal connection. This ideal listening mode is achieved through performative unplugging, whereby listening party attendees show their ability to delay gratification by turning off their phones. By unpacking the ideals constructed by the coloring book and listening party kit, we argue that the cultural values they seek to convey align with wider views about the power of podcasts to bring us together.